New Succinimide–Thiazolidinedione Hybrids as Multitarget Antidiabetic Agents: Design, Synthesis, Bioevaluation, and Molecular Modelling Studies - Mohammed A. Huneif; Mater H. Mahnashi; Muhammad Saeed Jan; Muhammad Shah; Sultan A. Almedhesh; Seham M. Alqahtani; Mohammad Jamaan Alzahrani; Muhammad Ayaz; Farhat Ullah; Umer Rashid; Abdul Sadiq (Molecules, 2023)
Diabetes mellitus (DM) is a metabolic disorder majorly arising from the pathophysiology of the pancreas manifested as a decline in the insulin production or the tissue’s resistance to the insulin. In this research, we have rationally designed and synthesized new succinimide–thiazolidinedione hybrids for the management of DM. In a multistep reaction, we were able to synthesize five new derivatives (10a–e). All the compounds were new containing a different substitution pattern on the N-atom of the succinimide ring. Initially, all the compounds were tested against the in vitro α-glucosidase, α-amylase, PTP1B, and DPP4 targets. In all of these targets, the compound 10d was observed to be the most potential antidiabetic agent. Based on this, the antidiabetic activity of the compound 10d was further investigated in experimental animals, which overall gave us encouraging results. The molecular docking studies of the compound 10d was also performed against the target enzymes α-glucosidase, α-amylase, PTP1B, and DPP4 using MOE. Overall, we observed that we have explored a new class of compounds as potential antidiabetic agents.